2015
DOI: 10.1681/asn.2014040332
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Acid Load Predicts ESRD among Adults with CKD

Abstract: Small clinical trials have shown that a reduction in dietary acid load (DAL) improves kidney injury and slows kidney function decline; however, the relationship between DAL and risk of ESRD in a population-based cohort with CKD remains unexamined. We examined the association between DAL, quantified by net acid excretion (NAE es ), and progression to ESRD in a nationally representative sample of adults in the United States. Among 1486 adults with CKD age$20 years enrolled in the National Health and Nutrition Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(113 citation statements)
references
References 28 publications
(24 reference statements)
5
103
0
5
Order By: Relevance
“…Their findings are supported by that of Scialla et al [21] who noted an association between higher NEAP and faster decline in kidney function among African Americans with hypertensive nephropathy. Additionally, an observational study by our group found an increased risk of CKD progression associated with higher baseline concentrations of dietary acid load [22] . We observed that in the US CKD population, higher levels of dietary acid load were associated with 3 times greater risk of ESRD as compared to those with lower levels (relative hazard (95% CI) 3.04 (1.58-5.86)).…”
Section: Dietary Acid Load and Ckd Progressionmentioning
confidence: 86%
“…Their findings are supported by that of Scialla et al [21] who noted an association between higher NEAP and faster decline in kidney function among African Americans with hypertensive nephropathy. Additionally, an observational study by our group found an increased risk of CKD progression associated with higher baseline concentrations of dietary acid load [22] . We observed that in the US CKD population, higher levels of dietary acid load were associated with 3 times greater risk of ESRD as compared to those with lower levels (relative hazard (95% CI) 3.04 (1.58-5.86)).…”
Section: Dietary Acid Load and Ckd Progressionmentioning
confidence: 86%
“…Eliichiro Kanda et al, study stated that patient with the lowest quartile of serum bicarbonate level show a high risk of chronic kidney disease progression compared with patients with high serum bicarbonate levels. [10][11][12][13][14][15] In present study group, many patients were in stage 4 and stage 5 have low serum bicarbonate level. Many patients in the study group had low serum bicarbonate level and only 07 patients were having high serum bicarbonate level who were in stage 3 and stage 4.…”
Section: No Of Patients 100%mentioning
confidence: 59%
“…Banerjee et al [26] have clearly shown that dietinduced acid load is associated with increased risk of ESRF. They demonstrated that worsening of metabolic acidosis was highly significantly associated with a decrease in GFR and concluded that acidosis in CKD is independently associated with an increased risk of ESRF.…”
Section: Acidosismentioning
confidence: 99%
“…They demonstrated that worsening of metabolic acidosis was highly significantly associated with a decrease in GFR and concluded that acidosis in CKD is independently associated with an increased risk of ESRF. [26] Secondly, a recent study from the University of Manchester, UK, showed that small changes in blood acidity are associated with an increase in parathyroid secretion, resulting in removal of calcium and phosphate from bones with arterial metastatic deposition. [27] The optimal NaHCO 3 dose remains to be determined, but the current recommendations state a dose of 0.5 -1.0 mmol of NaHCO 3 /kg body weight in three divided doses per day, i.e.…”
Section: Acidosismentioning
confidence: 99%